Using Internal Marketing Communications to Improve HRM in Service-Based Sports Organizations - Vlad I. ROȘCA (Revista de Management Comparat International)
This essay looks at how internal marketing can contribute to increasing the performances of sports organization. A particular component of the internal marketing paradigm receiving attention is communication. The paper analyses ideas about how learning from the general marketing theory can help sports club managers better communicate within their organization in order to enhance their personnel’s motivation and performances. The ultimate goals of sports clubs are winning success and delivering high value to the fans watching. An outward-inspired but inwardimplemented marketing pattern can help managers boost the performances of employees and of their organizations. In an intelligence-based, knowledge-driven economy, bench marking and best business practices can help improve a lot. Hence, the research aims to expand on a combination of general business allied theories and apply them to a sector that has received less attention in theory: performance sports.